VOCAL PRONUNCIATION IN CHORUS HARMONIZING IN SMK MUHAMMADIYAH I PALEMBANG - Irawan Sukma (Universitas Negeri Makassar, 2021)
ABSTRACTThe article entitled “Vocal Pronunciation in Chorus Harmonizing in SMK Muhammadiyah I Palembang “ is an analysis of the research of potential belonging to Muhsapa Voice members a high school choir in the vocal pronunciation to form the harmony of a choir group. The correct vocal pronunciation is how to form goodvowels in creatingneeded voices in choir and to form harmonies that do not use wertern musical concepts. The writer raises several questions in his formulated problems related to: (1) the avility to create a natural vical harmony. (2) the cocal pronunciation forproducing prime voice pronouns. (3) the benefits derived in the musical potential for choir anngioners. The study employed qualitative approach with the concept of phenomenology, ethnography, and the theory of musical harmony. The result of this study will be this: (1) the potential musical wings to produce powerful vowels and harmonies of correct vowels. (2) their potential can be used as a meanes for developing individual talents. Keywords: chorus, harmony, voice excellence, vocal pronunciation, prime vowels.